Striking a Balance between the Execution of Sentence and Pardon Implementation in Nigeria: A Way Forward - Ngwoke, Rita Abhavan; Oyinloye, Tawakaltu Queen; Eruteya, Ugiomo (Acta Universitatis Danubius. Juridica, 2024)
This paper aims to find a middle ground between sentencing and pardoning as procedures within Nigeria’s criminal justice system to enhance justice. As a contribution to the growing body of work challenging the perceived and actual disparities and increasing public outrage over recent high-profile pardons, this paper examines the historical precedent for tension between sentencing and executive pardon. Through a doctrinal research methodology, this paper discusses the Nigerian legal regimes on sentencing and pardoning and their major inconsistencies and absence of clear guidelines. Key findings in this paper suggest that the absence of adequate and transparent procedures in the matters of sentencing and pardoning results in whimsical decisions that are capable of undermining the credibility of the judiciary. The implications of this study are important for both the judicial and executive authorities, promoting changes to practices of both sentencing and pardoning so that they are dispensed fairly and equitably. This paper adds new knowledge to the current discourse on the need to achieve an equilibrium that can preserve judicial independence while making room for executive interference where necessary in the Nigerian criminal justice system.